Clinical Management of Pain in Rodents - Foley, Patricia L (Comp Med, 2019)
The use of effective regimens for mitigating pain remain underutilized in research rodents despite the general acceptance of both the ethical imperative and regulatory requirements intended to maximize animal welfare. Factors contributing to this gap between the need for and the actual use of analgesia include lack of sufficient evidence-based data on effective regimens, under-dosing due to labor required to dose analgesics at appropriate intervals, concerns that the use of analgesics may impact study outcomes, and beliefs that rodents recover quickly from invasive procedures and as such do not need analgesics. Fundamentally, any discussion of clinical management of pain in rodents must recognize that nociceptive pathways and pain signaling mechanisms are highly conserved across mammalian species, and that central processing of pain is largely equivalent in rodents and other larger research species such as dogs, cats, or primates. Other obstacles to effective pain management in rodents have been the lack of objective, science-driven data on pain assessment, and the availability of appropriate pharmacological tools for pain mitigation. To address this deficit, we have reviewed and summarized the available publications on pain management in rats, mice and guinea pigs. Different drug classes and specific pharmacokinetic profiles, recommended dosages, and routes of administration are discussed, and updated recommendations are provided. Nonpharmacologic tools for increasing the comfort and wellbeing of research animals are also discussed. The potential adverse effects of analgesics are also reviewed. While gaps still exist in our understanding of clinical pain management in rodents, effective pharmacologic and nonpharmacologic strategies are available that can and should be used to provide analgesia while minimizing adverse effects. The key to effective clinical management of pain is thoughtful planning that incorporates study needs and veterinary guidance, knowledge of the pharmacokinetics and mechanisms of action of drugs being considered, careful attention to individual differences, and establishing an institutional culture that commits to pain management for all species as a central component of animal welfare.